2013
DOI: 10.4240/wjgs.v5.i10.259
|View full text |Cite
|
Sign up to set email alerts
|

Post-colonoscopy appendicitis: A case report and systematic review

Abstract: Colonoscopy is a widely used diagnostic and therapeutic modality with a relatively low morbidity. However, given the large volume of procedures performed, awareness of the infrequent complications is essential. Perforation is an established complication of colonoscopy, and can range from 0.2%-3% depending on the series, population and modality of colonoscopy. Acute appendicitis after colonoscopy is an extremely rare event, and a cause-effect relationship between the colonoscopy and the appendicitis is not well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 25 publications
0
31
0
5
Order By: Relevance
“…3 Other proposed mechanisms include local oedema from trauma induced by the endoscope or intervention causing temporary obstruction of the appendiceal orifice. 4 It has also been suggested that excess pressure from the endoscope at the appendiceal lumen and possible excess inflation can result in inflammation secondary to trauma or promote the formation of a faecolith. 1,5–7…”
Section: Discussionmentioning
confidence: 99%
“…3 Other proposed mechanisms include local oedema from trauma induced by the endoscope or intervention causing temporary obstruction of the appendiceal orifice. 4 It has also been suggested that excess pressure from the endoscope at the appendiceal lumen and possible excess inflation can result in inflammation secondary to trauma or promote the formation of a faecolith. 1,5–7…”
Section: Discussionmentioning
confidence: 99%
“…Postcolonoscopy appendicitis should also be considered. It is such an unusual and extremely rare complicationthat causation by colonoscopy has not yet been adequately documented 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Although exceptionally infrequent, appendicitis can be seen as a complication of optical colonoscopy [34][35][36][37][38][39][40]. Only 28 cases of appendicitis as a complication of optical colonoscopy have been reported in the literature to our knowledge; the frequency has been estimated at 3.8 cases of appendicitis per 10,000 procedures [37,40].…”
Section: Appendicitismentioning
confidence: 99%
“…Only 28 cases of appendicitis as a complication of optical colonoscopy have been reported in the literature to our knowledge; the frequency has been estimated at 3.8 cases of appendicitis per 10,000 procedures [37,40]. The pathophysiology is not well understood, but a few mechanisms have been suggested.…”
Section: Appendicitismentioning
confidence: 99%
See 1 more Smart Citation